COMMUNITY POLICING AS PUBLIC PARTICIPATION STRATEGY FOR ENHANCING SECURITY IN KENYA - Kungu, David Mwangi (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Security is a basic necessity in every society as it is a watershed for development and prosperity in all sectors of the economy. However, for a long time this has been elusive both in the urban and rural areas. The insecurity experienced in many societies ranging from terrorism, cattle rustling to petty crimes has had devastating effects inducing loss of lives and massive destruction of property. In managing the security situation, the police resources in terms of personnel and equipment seem to have been strained as insecurity levels soar. It is believed that the criminals and perpetrators of insecurity live within same society and therefore, members of the society can identify them thus community policing was muted in Kenya. This study therefore, aimed at evaluating community policing as a security enhancing strategy. The study was guided by the Abraham Maslows hierarchy of needs which identifies security as a great concern which must be satisfied. The study adopted a case study research design with Koibatek District as the case. The target population for the study was 1679 members of community policing at the sub-location, location and Division levels, from which a sample of 265 was picked using stratified sampling, purposive sampling and simple random sampling. Data was collected using questionnaires and interviews and analysed descriptively where percentages and frequencies were computed and presented in tables, pie charts and graphs. The study established that there are community policing structures which have been clearly laid down at all levels as per the community policing manual. Further, community policing plays a significant role in reducing crime though riddled by a number of challenges such as mistrust and lack of capacity to handle crime. The study recommends that a strong partnership be created between the police and the members of the public and that capacity building through training is required to make the community policing committees effective.